2009
DOI: 10.1007/s10495-009-0339-5
|View full text |Cite
|
Sign up to set email alerts
|

Beta cell apoptosis in diabetes

Abstract: Apoptosis of beta cells is a feature of both type 1 and type 2 diabetes as well as loss of islets after transplantation. In type 1 diabetes, beta cells are destroyed by immunological mechanisms. In type 2 diabetes abnormal levels of metabolic factors contribute to beta cell failure and subsequent apoptosis. Loss of beta cells after islet transplantation is due to many factors including the stress associated with islet isolation, primary graft non-function and allogeneic graft rejection. Irrespective of the exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
143
0
6

Year Published

2010
2010
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 210 publications
(166 reference statements)
1
143
0
6
Order By: Relevance
“…3,[5][6][7]13,18,32 Here, we show that cytokines, palmitate and thapsigargin, induce Bax translocation, cytochrome c release and caspase-3 cleavage, independently of changes in Bcl-2, Bcl-XL, Bax and Bak expression levels, but partly as a consequence of Mcl-1 downregulation (Figure 8). Our data are in agreement with previous studies showing that Mcl-1, in spite of its preferential mitochondrial localization, 33 is able to prevent Bax activation and translocation.…”
Section: Pro-inflammatory Cytokines and Palmitate Decreasementioning
confidence: 58%
See 1 more Smart Citation
“…3,[5][6][7]13,18,32 Here, we show that cytokines, palmitate and thapsigargin, induce Bax translocation, cytochrome c release and caspase-3 cleavage, independently of changes in Bcl-2, Bcl-XL, Bax and Bak expression levels, but partly as a consequence of Mcl-1 downregulation (Figure 8). Our data are in agreement with previous studies showing that Mcl-1, in spite of its preferential mitochondrial localization, 33 is able to prevent Bax activation and translocation.…”
Section: Pro-inflammatory Cytokines and Palmitate Decreasementioning
confidence: 58%
“…1 The mitochondrial intrinsic pathway of apoptosis controlled by the B-cell lymphoma 2 (Bcl-2) protein family 2 plays a major role in pancreatic b-cell death in both T1D and T2D. 3 The Bcl-2 protein family can be divided into three groups, the antiapoptotic proteins (Bcl-2, B-cell lymphoma-extra large (Bcl-XL), Bcl-w, myeloid cell leukemia sequence 1 (Mcl-1) and A1), the multi-domain pro-apoptotic proteins (Bcl2-associated X protein (Bax), Bcl-2 homologous antagonist/killer (Bak) and Bok) and the pro-apoptotic BH3-only proteins (including Bim, Bid, neuronal death protein 5 (DP5, also known as Harakiri (Hrk)), Puma, Bad and Noxa). Upon death stimulus, Bax translocates from the cytosol to the mitochondria and oligomerizes with Bak, resulting in mitochondrial outer membrane permeabilization (MOMP).…”
mentioning
confidence: 99%
“…Collectively, these data suggest that apoptotic cells are captured consistently by dendritic cells, but induce dendritic-cell maturation and T cell cross-priming only in the presence of exogenous inflammatory mediators or CD4 + T cell help; otherwise, tolerance is induced [31]. Apoptosis is an important pathological component in many autoimmune diseases, including type 1 diabetes [32], and the requirement for additional 'danger' signals is often fulfilled in affected patients. Under these conditions, ubiquitous structural proteins can become the target of a secondary immune response, as exemplified by cytotoxic T lymphocyte (CTL) priming against vinculin from apoptotic cells [33].…”
Section: Discussionmentioning
confidence: 94%
“…CD8 + and CD4 + T cells, macrophages and dendritic cells induce beta cell demise by different mechanisms, such as perforin and granzyme B release, Fas-Fas ligand interaction and by secreting cytokines and free radicals inside and around the islets [7]. Production of inflammatory cytokines, such as IL-1β, IL-17, TNF and interferon-g (IFN-g), probably contribute to beta cell apoptosis in the early stages of the disease [8,9].…”
mentioning
confidence: 99%
“…Activation of the intrinsic apoptotic pathway is a key event in cytokine-mediated beta cell apoptosis [7,32,33], and overproduction of BCL-2 [34], BCL-XL [35] and MCL-1 prevents cytokine-induced apoptosis in vitro [28]. In vivo experiments, however, have shown that BCL-XL overproduction induces beta cell dysfunction [35], while increased production of BCL-2 is not sufficient to prevent autoimmune destruction of beta cells [36].…”
mentioning
confidence: 99%